A love for the earth: stories and experiences of the Beira Rio camp (Citizenship in Action: Extension and Culture Magazine, 2023)
In general, the project proposed the production of a video-documentary with testimonials of the residents of the Beira Rio Camp, in the city of Fronteira, in the state of Minas Gerais, which would bring an approach to their relations with natural resources and with the land, where the camp is. The learnings in school, the knowledge in everyday experiences, family experience, deterritorializations, among many other factors related to life in the field. It was also specifically aimed at verifying the changes that have occurred in the camp since the arrival of family farming, and the role of this model in the transformations of the site. And, finally, to have an overview of the natural resources used in production, to understand the expectations of residents on the more sustainable use of these resources. The testimonies were recorded, from a guide of questions, to facilitate the post-production process. The recordings made allowed to build a documentary with 34 minutes, which is being shown in schools in the region. Bringing the stories of the campers, and love they show for the land, to other audiences is an effective way to combat prejudice and misinformation on the members of the struggle for land movements. It is believed that the documentary "A love for the land" has fulfilled this function.
Keywords: natural resources; environment; video documentary